Synthesis and biological evaluation of memantine nitrates as a potential treatment for neurodegenerative diseases12. Issue 1 (1st November 2016) - Liu, Zheng; Yang, Si; Jin, Xiaoyong; Zhang, Gaoxiao; Guo, Baojian; Chen, Haiyun; Yu, Pei; Sun, Yewei; Zhang, Zaijun; Wang, Yuqiang
Abstract : A series of memantine nitrate derivatives, as dual functional compounds with neuroprotective and vasodilatory activity for neurodegenerative diseases, was designed and synthesized. Abstract : A series of memantine nitrate derivatives, as dual functional compounds with neuroprotective and vasodilatory activity for neurodegenerative diseases, was designed and synthesized. These compounds combined the memantine skeleton and a nitrate moiety, and thus inhibited the N -methyl-d -aspartic acid receptor and released NO in the central nervous system. The biological evaluation results revealed that the new memantine nitrates were effective in protecting neurons against glutamate-induced injury in vitro . Moreover, memantine nitrates dilated aortic rings against phenylephrine-induced contraction. The structure–activity relationships of neuroprotection and vasodilation were both analyzed. In further studies, compoundMN-05 significantly protected cortical neurons by inhibiting Ca 2+ influx, reducing free radical production and maintaining the mitochondrial membrane potential. Further research onMN-05 is warranted.